Sound localization and quantification analysis of an automotive engine cooling module. (20th January 2022) - Amoiridis, O.; Zarri, A.; Zamponi, R.; Pasco, Y.; Yakhina, G.; Christophe, J.; Moreau, S.; Schram, C.
Abstract: Sound emissions of an automotive engine cooling system are studied using both single-microphone directivity measurements and a rotating beamforming technique. These measurements provide reference acoustic data on such a system and some new understanding of the effect that the radiator induces on the distribution of sound sources. Indeed, the beamforming results indicate that, above the frequency limit allowed by the Rayleigh criterion, it is possible to localize and quantify the noise sources even through the heat-exchanger core. Moreover, for the investigated operating points along the fan performance curve, the sources are always distributed at the tip of the blades and, in particular, at the leading edge. The present evidence, confirmed by the similar trends of the frequency spectra with and without the heat exchanger, leads to the conclusion that the dominant sound mechanism is the turbulence-interaction noise. Nevertheless, this turbulence is produced within the gap between the fan ring and its casing rather than generated by the radiator core. The latter appears to induce negligible acoustic transmission losses but, more significantly, is found to have a minimal influence on the aerodynamic modification of sound sources for all the analyzed operating conditions.